Pemanfaatan Adobe Animate dalam Pengembangan Media Pembelajaran Interaktif Konsep Listrik dan Konduktivitas Untuk Siswa Sekolah Dasar Negeri 4 Banda Aceh - Al Fajar, Johan; Alfina; Lidiana (Jurnal Sistem Komputer (SISKOM), 2023)
This research aims to develop and evaluate interactive learning media that uses Adobe Animate to teach electricity and conductivity concepts to students at State Elementary School 4 Banda Aceh. This interactive learning media is designed to increase students' interest and understanding of science subject matter. The development method used includes the design stage, content development, and testing on a group of students. The development of this learning media is based on constructivist learning theory and an interactive learning approach. Adobe Animate is used as a tool to create interesting animations, simulations and interactions, with the aim of making it easier for students to understand abstract concepts such as conductors, insulators, electric currents and circuits. Testing of learning media was carried out through trials on students in Banda State Elementary School 4 class. Aceh. The test results show that this interactive learning media is able to increase students' interest and understanding of the concepts of electricity and conductivity. Students show more active participation, and are able to better explain the concepts taught through this interactive media. This research indicates that the use of interactive learning media using Adobe Animate can be an effective alternative in supporting the learning of electricity and conductivity concepts at the school level Base. The implications of this research provide guidance for further development of interactive learning media in an effort to improve the quality of science learning for elementary school students.